SYNTHESIS AND SWELLING PROPERTIES OF CHITOSAN-BASED HYDROGELS CROSSLINKED FORMALDEHYDE AND TRIPOLYPHOSPHATE - Ramadhani, Fadilah; Pasaribu, Subur P.; Panggabean, Aman Sentosa (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Hydrogel is a hydrophilic polymer network that can experience swelling with the ability to absorb and retain large amounts of liquid without decomposing and is widely applied in the fields of health, environment and agriculture. The swelling properties of hydrogels are influenced by the type of tissue and the density of crosslinks that form it. In this study the hydrogel was prepared by stirring a 2% chitosan solution (w/v) as much as 7 mL with 3 ml of formaldehyde-tripolyphosphate crosslinking mixture at variations of 3:0, 2:1, 1:1, 1:2 and 0:3 (v/v) at room temperature and swelling tests were carried out by immersing each hydrogel produced in aquades for a span of 24 hours at the same temperature. Based on the observations, the gel formation time was 420, 97, 84, 75 and 58 minutes respectively which showed the lower the chitosan concentration and the higher the tripolyphosphate, the faster the gel formation process. Then the degree of consecutive sweling was 581.43; 78,23; 75,17; 48.85 and 20.97% (w/w) indicate that covalent cross-networks formed by amine groups on chitosan with aldehyde groups on formaldehyde are more stable and more difficult to degrade than physical cross-networks formed by groups on chitosan and tripolyphosphates. Keywords: Hydrogel, Crosslinking, Chitosan-tripolyphosphate, Degree of swelling.